2020
DOI: 10.1111/mcn.12770
|View full text |Cite
|
Sign up to set email alerts
|

Reducing malnutrition in Cambodia. A modeling exercise to prioritize multisectoral interventions

Abstract: Undernutrition is a major contributor to child morbidity and mortality and poses a large burden to the economy, in Cambodia. This study explored factors contributing to child stunting and wasting and their regional inequalities among 1,938 Cambodian children aged 6–23.9 months. Data were drawn from a longitudinal study (year 2017) conducted in six districts of two north‐eastern provinces and the capital and used as cross‐sectional. Socio‐demographic and household characteristics, children's feeding practices d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 40 publications
(46 reference statements)
0
11
0
1
Order By: Relevance
“…The existence of clear responsibilities in resources, leadership, and governance between sectors in nutrition-specific and -sensitive interventions has a strong potential to support the acceleration of stunting reduction [ 33 ]. The developed strategy is carried out through collaborations and coordination across sectors at the central and regional levels, as well as through the provision of sustainable food, health, water, and nutrition [ 34 ]. Multisectoral action plans at various levels have been proven to reduce stunting [ 33 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The existence of clear responsibilities in resources, leadership, and governance between sectors in nutrition-specific and -sensitive interventions has a strong potential to support the acceleration of stunting reduction [ 33 ]. The developed strategy is carried out through collaborations and coordination across sectors at the central and regional levels, as well as through the provision of sustainable food, health, water, and nutrition [ 34 ]. Multisectoral action plans at various levels have been proven to reduce stunting [ 33 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…That limited evidence of effectiveness stressed the need to focus on household water practices (Clasen et al, ). Source of drinking water has shown to be a key contributor to child wasting in the north‐eastern provinces (Laillou et al, ) supporting the importance of water hygiene promotion in households and communities as part of a comprehensive approach for ensuring good child nutritional status.…”
Section: Discussionmentioning
confidence: 99%
“…Of the two predictors classified in this factor, low micronutrient quality is the predictor that appears to provide the greatest increased risk of causing stunting, which is equal to 13% ( 33 ) . Although few studies have reported it, it was identified that vitamin D ( 19 ) , iodine ( 33 ) , iron ( 28 ) , and vitamin A ( 31 , 33 ) are micronutrients associated with stunting in Southeast Asia. This finding is also the same as that of another study on stunting in other middleand low-income countries ( 48 ) .…”
Section: Discussionmentioning
confidence: 99%